2022
DOI: 10.21873/invivo.13021
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Quality and Distribution of Adipose Tissue in Patients With Primary Central Nervous System Lymphoma

Abstract: Background/Aim: Body composition assessment has shown promising results as a prognostic biomarker as depicted by cross-sectional imaging of several tumor entities including lymphomas. The present study sought to elucidate the prognostic relevance of subcutaneous and visceral fat tissue (SAT and VAT) in patients with primary central nervous system lymphoma (PCNSL). Patients and Methods: Overall, 74 patients (36 female patients, 46.7%) with a mean age of 64.2±12.8 years (range=23-81 years) were identified in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Hinnerichs et al evaluated the prognostic role of VAT and SAT in 74 patients with primary central nervous system lymphoma (PCNSL) [ 22 ]. Quantification of VAT and SAT was performed on the axial plane on CT images at L3 vertebra level.…”
Section: Abdominal Adipose Tissue Quantification and Distribution In ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Hinnerichs et al evaluated the prognostic role of VAT and SAT in 74 patients with primary central nervous system lymphoma (PCNSL) [ 22 ]. Quantification of VAT and SAT was performed on the axial plane on CT images at L3 vertebra level.…”
Section: Abdominal Adipose Tissue Quantification and Distribution In ...mentioning
confidence: 99%
“…The VAT/SAT ratio was then calculated. This study demonstrated no correlation between adipose tissue parameters measured with either overall survival or progression-free survival in PCNSL patients, suggesting that these parameters cannot be used as reliable biomarkers for PCNSL [ 22 ].…”
Section: Abdominal Adipose Tissue Quantification and Distribution In ...mentioning
confidence: 99%